Предмет: Алгебра,
автор: tkachenko199903
Решить уравнение. (x-3) (x2+x)-(3x-9) (x+1)=0
Помогите пожалуйста)
Ответы
Автор ответа:
0
(x-3)(x2+x)-(3x-9)(x+1)=0
(x^2*2+x^2-3x2-3x)-(3x^2+3x-9x-9)=0
x^2*2+x^2-3x2-3x-3x^2-3x+9x-9=0
x^2*2+6x-11=0
(x^2*2+x^2-3x2-3x)-(3x^2+3x-9x-9)=0
x^2*2+x^2-3x2-3x-3x^2-3x+9x-9=0
x^2*2+6x-11=0
Похожие вопросы
Предмет: Английский язык,
автор: nestet09
Предмет: Литература,
автор: geroihappy
Предмет: Литература,
автор: sarxan812
Предмет: Алгебра,
автор: kristinalol123
Предмет: Информатика,
автор: Аноним